Digital leadership in the academic environment: A systematic literature review - Asem S. Obied (Social Sciences and Humanities Open)
This paper describes digital leadership in academic environments, addressing many challenges that require institutions to communicate information technology effectively. While the development of digital transformation in academia is currently becoming necessary, these initiatives depend on the technologies and the leadership guiding them. It sets out to synthesize extant research in the domain of digital leadership within academia, which assesses the current knowledge and scoping for future research possibilities. The systematic literature review examined 50 articles from leading academic journals representing publications from 2019 through 2024. The current study emphasizes that effective leadership, good governance, connectedness, and relational capital remain important variables affecting successful collaborative outcomes.Moreover, the paper identifies how national cultures influence perceptions and responses to digital leadership, highlighting the need for cultural nuance in strategies. The review makes a substantial contribution to our knowledge of the pivotal role of digital leadership in academia by shedding light on the opportunities and challenges arising from the process of digital evolution, as well as its impact on personnel and institutions. The methodology of this research was a critical exploration of the literature, focusing on how digital leadership has been conceptualized and contextualized in the academic environment. This paper concludes by making a case for the necessity of leaders who can understand the digital landscape and thereby enable academic organizations to adapt and thrive in today's increasingly digital world.